Evaluating the effectiveness of common aerospace materials at lowering the whole body effective dose equivalent in deep space. (December 2019) - Bond, D.K.; Goddard, B.; Singleterry, R.C.; Bilbao y León, S.
Abstract: Materials have a primary purpose in the design of space vehicles, such as fuels, walls, racks, windows, etc. Additionally, each will also affect space radiation protection. The shielding capabilities of 59 materials are evaluated for deep space travel, in terms of whole body effective dose equivalent and # o f N u c l e o n s V o l u m e . The hydrogen rich materials are evaluated further using # o f H y d r o g e n A t o m s M a s s and # o f H y d r o g e n A t o m s V o l u m e . All evaluated materials, through density, composition, and shielding ability, can be categorized into three groups: metals, polymers and composites, and fuels, hydrides, and liquid gases. The analyses presented in the article shows that a "magic" material is not possible; however polymers and composites should be used instead of metals, if they can serve their primary purpose. Polyethylene and magnesium borohydride are shown to be the best feasible materials from this sample. Thermal neutron absorbers, 6 Li and 0 B 1, do not have a significant effect on E D . Alloying of materials, such as aluminum, for strengthening purposes, do not increase E D . Ultimately, a space vehicle is a system of systems and radiation protection must be one of them. Highlights: Polymers and composites should be used instead of metals, if primary purpose is met. Polyethylene and magnesium borohydride are shown to be the best feasible materials. Thermal neutron absorbers do not have a significant effect on exposure. Alloying of materials, for strengthening purposes, do not increase exposure. Hydrogen storage improves shielding ability if 14.4 wt percent or greater.